The new advisor for life : become the indispensable financial advisor to affluent families - Gresham, Stephen D.; Gresham, Stephen D. (Hoboken, N.J : Wiley, 2012)
'Expert advice on building an unshakable foundation as a financial advisor to the eliteThe revised and updated edition of the definitive guide to growing and maintaining a financial advice firm, The New Advisor for Life explores the fallout of the market crash on up-and-coming advisors. With a particular focus on the generation X and Y concern with debt management and long-term investment, this new edition examines what young investors look for in an advisor. Today, more than ever, insight, analysis, and validation are valued, but to be truly successful, an advisor needs to walk the line between being well-informed but not appearing condescending. What today's investors want in a financial advisor is someone who can cut through the noise and clutter of the financial services industry and the mainstream media Covers the basics, from setting a client's investment goals, selecting complementary investments, and monitoring portfolio balance, to the advanced--developing a personal finance plan for your clients based on their specific needs VP of Fidelity Investments Steve Gresham presents a 19-point checklist for financial advisors to offer their clients'life advice' Keeping clients engaged is more important than ever, and The New Advisor for Life gives the aspiring financial advisor the secrets to success normally reserved for the country's top firms'--
Rev. ed. of: Advisor for life. 2007.
Includes index.
Keywords: Financial planners; Investment advisors; Affluent consumers -- Finance, Personal; BUSINESS & ECONOMICS / Finance